The Effectiveness of STEAM-Based Augmented Reality Media in Improving the Quality of Natural Science Learning in Elementary School - Idam Ragil Widianto Atmojo; Roy Ardiansyah; Dwi Yuniasih Saputri; Fadhil Purnama Adi (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study describes the effectiveness of STEAM-based augmented reality (AR) learning media in natural science learning in elementary schools. This research used an experimental method. Six schools were involved as the subjects of this research, which was consisted of 3 elementary schools for experimental classes (60 students) and three elementary schools for control classes (60 students). The teachers involved were the 6th grader teachers. The data collection technique used 30 multiple choices questions for the students.The study results concluded that STEAM-based augmented reality effectively improved the quality of natural science learning in elementary schools. The t-test calculation results utilizing SPSS obtained t-count of 2.874 t-table of 1.980 (df-2= 122-2= 120). The normalized gain results showed a significant increase before and after using STEAM-based augmented reality media in natural science learning in elementary schools, which was 0.72 included in the high category.This research implies that research helps teachers optimize the use of media and teaching approaches. One of them is the use of STEAM with augmented reality media.